Economics of Mercantile Credit: A Study in Methodology - Reinhardt, Hedwig (The Review of Economics and Statistics, 1957)
Tp HE sales-oriented American economy relies on credit for nine-tenths of its transactions at the business level. Not on bank credit, consumer credit, real estate credit, investment credit; some producers and distributors can do without them, important as they all are. But today's business cannot be carried on without mercantile credit, which is extended by manufacturers and wholesalers to their business customers. No supplier can abstain from offering and no buyer from taking it. There are but few exceptions to this rule. Mercantile credit, therefore, has become a matter of life and death for the modern economy. The volume of mercantile credit is hardly matched by any other kind of credit. Around $300 billion a year may have been used in the 'decade following World War II.V In view of the fact that mercantile credit is generally given on short terms, the total of $300 billion covers a huge number of single credit transactions at a rapid turnover rate another striking feature of this form of credit. Amounts outstanding at any one time (receivables), furthermore, fluctuate in close response to business conditions and become a barometer of the economic atmosphere. There is sufficient evidence of the dominant role of mercantile credit. But what is its meaning in terms of the economic process? 2